2019
DOI: 10.15388/psichol.2018.4
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Creativity and Global/National Identity: Comparative Study of Lithuanian and American Students’ Sample

Abstract: The mindset of either a national or global identity was primed in the participants in the United States and Lithuania. The effects of priming on creativity were then examined. Two hundred and eighty-five participants from the United States and 95 Lithuanian participants received one of three possible manipulations: one that primed national identity, one that primed global identity, or no manipulation. They were then asked to complete measures of creativity. The results suggested that participants from Lithuani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 13 publications
(19 reference statements)
0
5
0
Order By: Relevance
“…Tidikis and Dunbar (2019) found that global citizenship predicted creativity in different domains (i.e., everyday, scholarly and mechanic/scientific creativity). In contrast, Tidikis et al (2018) showed that a global prime condition increased creativity only among US participants, while national ethnic identification increased creativity among Lithuanian participants. In any case, with the exception of biculturalism, cultural identity processes have rarely been considered to shape creative behavior directly (Gläveanu and Tanggaard, 2014), and, to our knowledge, the role of global vs. ethnic culture identification, or global vs. host culture identification (e.g., in migrants) have not been considered in tandem.…”
Section: Creativity As a Potential Outcome Of Identification Processesmentioning
confidence: 78%
See 3 more Smart Citations
“…Tidikis and Dunbar (2019) found that global citizenship predicted creativity in different domains (i.e., everyday, scholarly and mechanic/scientific creativity). In contrast, Tidikis et al (2018) showed that a global prime condition increased creativity only among US participants, while national ethnic identification increased creativity among Lithuanian participants. In any case, with the exception of biculturalism, cultural identity processes have rarely been considered to shape creative behavior directly (Gläveanu and Tanggaard, 2014), and, to our knowledge, the role of global vs. ethnic culture identification, or global vs. host culture identification (e.g., in migrants) have not been considered in tandem.…”
Section: Creativity As a Potential Outcome Of Identification Processesmentioning
confidence: 78%
“…This translates into a high relationship focus that makes them better at generating relationships between loosely connected ideas, which is also the basis for creativity. attachment or constructive patriotism (i.e., love for one's country) vs. glorification or superiority of one's home nation over other nations (see Clerkin, 2013;Tidikis et al, 2018). Only a few recent studies examine the associations between global or local (ethnic) identifications and creativity, and results are inconclusive.…”
Section: Creativity As a Potential Outcome Of Identification Processesmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, research has highlighted the relationship between mathematical creative thinking (MCT) and students' overall competence and sense of identity within their cultural environment (Hongjia et al, 2018). Hence, MCT is not only an academic pursuit but also a means of strengthening students' affiliation with their ethnicity and culture (Soler Pastor et al, 2022;Tidikis et al, 2018). Despite these insights, the factors influencing student creativity, particularly in mathematics, remain unclear (Liu et al, 2021;Power, 2015;RN Wang & Chang, 2022;Wu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%